2018
DOI: 10.1161/circimaging.117.007107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Coronary Artery Stenosis by Quantitative Flow Ratio During Invasive Coronary Angiography

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
189
4
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 191 publications
(213 citation statements)
references
References 32 publications
16
189
4
4
Order By: Relevance
“…The diagnostic performance of QFR with FFR as reference is well documented in patients with stable angina . Our data indicate that QFR might also be a valuable tool in the evaluation of NCLs in patients with acute STEMI undergoing primary PCI.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The diagnostic performance of QFR with FFR as reference is well documented in patients with stable angina . Our data indicate that QFR might also be a valuable tool in the evaluation of NCLs in patients with acute STEMI undergoing primary PCI.…”
Section: Discussionmentioning
confidence: 56%
“…The complete list of anatomical and angiographic exclusion criteria is presented in Supporting Information Table S1. These criteria for QFR analysis match those of prior QFR studies …”
Section: Methodsmentioning
confidence: 86%
“…The higher accuracy (92.7%) in FAVOR II China may be explained by the smaller number of lesions with FFR values close to the FFR 0.80 cutpoint. Results in both studies showed improved performance of QFR compared with early validation studies on offline computation of QFR 11, 15. The improved precision may be facilitated by the online analysis setup with instant feedback between operator and analyst.…”
Section: Discussionmentioning
confidence: 86%
“…Secondary outcome measures included sensitivity; specificity; summary of the receiver‐operator characteristics curve (sROC); negative predictive value; positive predictive value, positive likelihood ratio; negative likelihood ratio, and identification of independent predictors for increased QFR‐FFR difference using predefined clinical and lesion characteristics: age; body mass index (BMI); diabetes mellitus; sex; hypertension; family history of coronary artery disease (CAD) previous myocardial infarction; previous PCI; current smoking; lesion location; FFR; % DS (two‐dimensional quantitative coronary angiography [2D‐QCA]); % DS (three‐dimensional quantitative coronary angiography [3D‐QCA]); lesion length (2D‐QCA), and 95% hybrid limits. The strategy for calculation of 95% hybrid limits was previously described in detail …”
Section: Methodsmentioning
confidence: 99%
“…To improve access to functional lesion evaluation during invasive coronary angiography, quantitative flow ratio (QFR) based on three‐dimensional reconstruction of coronary arteries and application of mathematical equations was recently developed. Validation of QFR in mid‐sized prospective studies showed good diagnostic accuracy of QFR in core‐lab and in‐procedure settings using FFR as the reference standard with an overall classification agreement ranging between 80 and 90% . In this systematic, individual participant data meta‐analysis based on prospective studies, we aimed to evaluate the diagnostic performance of the CE‐marked QFR algorithm (Medis medical imaging b.v. and Pulse Medical Imaging Technology Co.) and identify predictors for discrepancy between QFR and FFR.…”
Section: Introductionmentioning
confidence: 99%